Attribute misreporting and appraisal bias - Eriksen, Michael D; Kuang, Chun; Zhu, Wenyu (Review of Finance, 2024)
Abstract We assemble a property-level panel of appraiser-reported attributes associated with 4.6 million loan applications from 2013 to 2017 to test whether attributes were consistently reported. Appraisers have an incentive to misreport property attributes to justify higher appraised values to ensure that associated mortgage loans are approved. We focus on property transactions with multiple sets of attributes reported by the same appraiser within four quarters and find evidence consistent with an intent to inflate valuations through attribute misreporting. We find that strategic misreporting of attributes is prevalent across markets, and that highly leveraged borrowers whose appraisals had inconsistently reported attributes were 9.8 percent more likely to become seriously delinquent in their loan payments.